Notothylas javanica (Anthocerotophyta: Notothyladaceae): a new record for the bryoflora of Mexico - Escolástico-Ortiz, Dennis Alejandro; Juárez-Martínez, Catalina (Instituto de Ecología, A.C., 2018)
Background and Aims: Reports on the genus Notothylas for Mexico are scarce and are known only from few published records and herbarium specimens. This work reports for the first time Notothylas javanica in Mexico.Methods: Morphological characters of Notothylas javanica were examined under the stereo, compound and scanning electron (SEM) microscopes. Specimens collected were deposited in MEXU.Key results: This work provides descriptions, illustrations and ecological data for the species. Differences and similarities with the other species of Notothylas reported for Mexico are discussed. In addition, an identification key for the Mexican species of Notothylas is provided.Conclusions: Information compiled for Notothylas suggests that at least three species occur in Mexico. To increase the knowledge of the genus in this country, there is a need for further exploration of key areas and, additional studies on its diversity, ecology and geographical distribution.